Intra aortic balloon pump: literature review of risk factors related to complications of the intraaortic balloon pump - Parissis, Haralabos (BioMed Central, 2011)
The increasing use of the intra aortic balloon pump is attributed to the relatively easy percutaneous insertion and the low threshold of use over the past few years, especially in elderly patients with multi-vessel diseases and an affected ejection fraction. Unfortunately, the clinical assessment of the complications associated to the use of this supporting device, underestimates the frequency of such complications. This report has looked at the current literature and attempt to identify incremental risk factors related to the development of adverse effects during support with an intaaortic balloon pump. The paper concludes that in contrary to early reports, newer studies have shown that complications following intraaortic balloon pump treatment, is decreasing. Moreover the literature suggests that the thrombosis and infective complications are relevant to the duration of the pump treatment, while the ischemic problems of the limbs are mostly linked to the atherosclerotic status of the common femoral artery.